UJI BEBERAPA KONSENTRASI EKSTRAK UMBI GADUNG (Dioscorea hispida Dennst) TERHADAP HAMA KEONG MAS (Pomacea canaliculata L.) - Alfaizal; Hafiz Fauzana; Desita Salbiah (DINAMIKA PERTANIAN, 2021)
Riau is one of a lowland rice producing provinces. One of the pests that can reduce rice productivity is the golden snail (Pomacea canaliculata L.). The solution for controlling the golden snail (P. canaliculata L.). Pest uses environmentally friendly control techniques, namely botanical pesticides of gadung tubers. This study aims to obtain a concentration of the extract of gadung tuber flour (Dioscorea hispida Dennst) which is effective in controlled the attack of golden snails (P. canaliculata L.) in lowland rice plants. This research was conducted experimentally using completely randomized design (CRD) consisting of five treatments and four replications, in order to obtain 20 experimental units. The treatments consisted of concentrations of gadung tubers extract, namely 0 g.l-1, 25 g.l-1, 50 g.l-1, 75 g.l-1, and 100 g.l-1. Observations included the initial dst time to snail death, lethal time 50 (LT 50), daily total mortality, and behavior changes in behavior. The results showed that the application of 100 g.l concentration of gadung tuber extract treatment caused the highest total mortality of golden snails (P. canaliculata L.) of 74.99%, but it was not effective yet in controlling the golden snail pest because it was not able to kill the golden snail above 80%.